Further studies on harvestman genus Homolophus (Opiliones: Phalangiidae), with descriptions of two new species - Snegovaya, Nataly Yu.; Cokendolpher, James C. (Zootaxa, 2021)
A key to the members of the subfamily Opilioninae is presented, including the genus Homolophus. That same genus is briefly reviewed, diagnosed, and redescribed based upon a study of approximately half of the described species. Many older museum specimens from the Zoological Institute (Saint-Petersburg, Russia) were identified and all species present were redescribed. A list of the 29 currently accepted species (all from Northeastern and Central Asia) is presented along with a list of another four species that their validity and proper inclusion in the genus are questioned (still need to be investigated extensively). Descriptions and redescriptions with many illustrations are presented for two new species and 15 previously described species of Homolophus: H. albofasciatus (Kulczyński, 1901); H. almasyi (Roewer, 1911); H. andreevae Staręga & Snegovaya, 2008; H. arcticus Banks, 1893; H. asiaticus (Gricenko, 1979a); H. betpakdalensis (Gricenko, 1976); H. charitonovi (Gricenko, 1972); H. chemerisi Staręga & Snegovaya, 2008; H. chevrizovi Staręga & Snegovaya, 2008; H. gobiensis Tsurusaki, Tchemeris & Logunov, 2000; H. kozlovi sp. nov.; H. martensi (Staręga, 1986); H. milkoi sp. nov.; H. nordenskioeldi (L. Koch, 1879a); H. pallens (Kulczyński, 1901); H. silhavyi Staręga & Snegovaya, 2008; H. tibetanus (Roewer, 1911); H. vladimirae (Šilhavý, 1967). New country distributional records are detailed for nine species, not including those for the two new species. Three new combinations with Homolophus (H. almasyi, H. asiaticus, H. charitonovi) are recognized for Opilio almasyi Roewer, 1911, Opilio asiaticus Gricenko, 1979a, and Globipes charitonovi Gricenko, 1972.